Kawasaki-Like Syndrome as an Emerging Complication of SARS-CoV-2 Infection in Young Adults - Germano, N (2020)
Background: Kawasaki-like syndrome occurring in children during the COVID-19 pandemic has been labelled multisystem inflammatory syndrome in children (MIS-C) by the CDC and paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 infection (PIMS-TS) by the ECDC. Case report: We report the case of an 18-year-old male patient presenting with a 72-hour history of abdominal pain, fever, erythematous skin rash, vomiting and diarrhoea. Examination showed he also had shock and he was first thought to have oedematous cholecystitis. SARS-CoV-2 infection was also diagnosed. He was admitted to the ICU, and echocardiography showed cardiac dysfunction, with a low ejection fraction and low cardiac index. High-sensitivity troponin serum levels were elevated. The patient received inotropic and vasopressor support. As he fulfilled several criteria for MIS-C/PIMS-TS, he was administered acetylsalicylic acid, corticosteroids and immunoglobulin, with a good clinical response. Conclusion: This case emphasizes how this severe presentation of COVID-19 can easily be misdiagnosed if the clinician is less aware of this syndrome in younger patients. Learning points: SARS-CoV-2 infection is a diagnostic challenge in some patients with atypical clinical presentations, who may have MIS-C/PIMS-TS.Physicians should be aware of this condition when evaluating teenagers and young adults with COVID-19.